The relationship between disease severity and defense mechanisms in fibromyalgia syndrome - Berk, Ejder; Baykara, Sema (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2020)
Objectives: The aim of the present study was to investigate the possible relationship between the disease severity and defense mechanisms in fibromyalgia syndrome (FMS) and to contribute to the clarification of the etiopathogenesis of FMS. Patients and methods: A total of 103 female patients (mean age: 42.6 +/- 10.0 years; range, 20 to 67 years) diagnosed with primary FMS based on the 2016 revised American College of Rheumatology (ACR) diagnostic criteria and without any psychiatric diagnosis were included in the study. A semi-structured sociodemographic and clinical data form was used. The Fibromyalgia Impact Questionnaire (FIQ), Defense Style Questionnaire-40 (DSQ-40), Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) were applied to all patients. Based on the FIQ scores, the patients were divided into two groups as mild-moderate (<70) and severe (>7O) FMS groups. Results: There were 56 patients in the mild-moderate FMS group and 47 patients in the severe FMS group. As FIQ scores increased, sublimation (r=0.204, p=0.030) and mature factor (r=0.229, p=0.020) scores decreased, and projection (r=0.210, p=0.033) and somatization (r=0.287, p=0.003) scores increased. Pseudoaltruism (p=0.043), displacement (p=0.026), and somatization (p=0.021) scores were higher in the severe FMS group. The BDI and BAI scores were also higher in the severe FMS group, compared to the mild-moderate FMS group (p=0.001 and p=0.002, respectively). Conclusion: Our study results show that there is a significant correlation between the increased disease severity, decreased mature defense mechanisms, and increased immature defense mechanisms in FMS patients.
Keywords: Defense mechanisms; fibromyalgia; severity of illness index; surveys and questionnaires